Electrical impedance spectroscopy significantly enhances correct biopsy choice for pigmented skin lesions beyond clinical evaluation and dermoscopy. Issue 1 (13th October 2022) - Zakria, Danny; Brownstone, Nicholas; Han, Joseph; Owji, Shayan; Dirr, McKenzie; Rigel, Darrell
Abstract : The purpose of this study was to investigate whether EIS technology can further improve correct biopsy choices beyond clinical and dermoscopic evaluation for melanoma (MM), severe dysplastic nevi (SDN) and benign PSLs. Images of 49 MMs, SDNs and benign PSLs were randomly selected from a prior study and were provided in a reader-type survey study to dermatologists to evaluate for biopsy. A total of 33, 957 biopsy decisions were analyzed. Respondents significantly improved on the correct biopsy choice with the addition of dermoscopy versus clinical image alone for melanoma and severely dysplastic nevi. Respondents also showed a statistically significant improvement in correct biopsy choice beyond their dermoscopic evaluation when integrating the EIS score versus dermoscopy with clinical images for MM, SDN and benign lesions. Respondents also made fewer incorrect biopsy choices with the addition of the EIS score versus dermoscopy and clinical image for MM and benign lesions. Sub-analyses of biopsy choices were also conducted based on experience and practice type. The findings from this study demonstrate that the integration of EIS technology into PSL biopsy decisions has the potential to significantly improve the accuracy of lesion selection for biopsy beyond clinical and dermoscopic evaluation alone.